The extraction of wood in fixed bed and atmospheric condition - Gürkahraman, Melek; Pehlivan, Dursun (Scientific and Technical Research Council of Turkey, 1999)
Extraction of poplar wood chips with ethanol in a fixed bed and in a soxhlet apparatus in atmosferic conditions was studied. The fixed-bed extraction of the wood was carried out at 30°C and 70°C bed temperatures. The conversion rates of wood (daf basis) were determined from the decrease in the amounts of wood in the bed. The extract yield obtained in a fixed bed was 6.45% at 30°C and 7.44% at 70°C. The yield reached 6.02% in a soxhlet apparatus. FTIR and TGA analyses of the extracts were also undertaken. The FTIR spectra of the extracts indicated mainly lignin and hemicellulose properties. The TGA patterns showed that the lignin components transfered into the extracts were decomposed first.; Extraction of poplar wood chips with ethanol in a fixed bed and in a soxhlet apparatus in atmospheric conditions was studied. The fixed-bed extraction of the wood was carried out at 30 °C and 70 °C bed temperatures. The conversion rates of wood (daf basis) were determined from the decrease in the amounts of wood in the bed. The extract yield obtained in a fixed bed was 6.45% at 30 °C and 7.44% at 70 °C. The yield reached 6.02% in a soxhlet apparatus. FTIR and TGA analyses of the extracts were also undertaken. The FTIR spectra of the extracts indicated mainly lignin and hemicellulose properties. The TGA patterns showed that the lignin components transferred into the extracts were decomposed first.
Odunun sabit yatak ve atmosferik sartlarda ekstraksiyonu
Keywords: Ethanol; Extraction; FTIR; TGA; Wood